Artificial biosynthesis of phenylpropanoic acids in a tyrosine overproducing Escherichia coli strain - Sun-Young Kang; Oksik Choi; Jae Kwan Lee; Bang Yeon Hwang; Tai-Boong Uhm; Young‐Soo Hong (2012)
Abstract Background The phenylpropanoid metabolites are an extremely diverse group of natural products biosynthesized by plants, fungi, and bacteria. Although these compounds are widely used in human health care and nutrition services, their availability is limited by regional variations, and isolation of single compounds from plants is often difficult. Recent advances in synthetic biology and metabolic engineering have enabled artificial production of plant secondary metabolites in microorganisms. Results We develop an Escherichia coli system containing an artificial biosynthetic pathway that yields phenylpropanoic acids, such as 4-coumaric acid, caffeic acid, and ferulic acid, from simple carbon sources. These artificial biosynthetic pathways contained a codon-optimized tal gene that improved the productivity of 4-coumaric acid and ferulic acid, but not caffeic acid in a minimal salt medium. These heterologous pathways extended in E. coli that had biosynthesis machinery overproducing tyrosine. Finally, the titers of 4-coumaric acid, caffeic acid, and ferulic acid reached 974 mg/L, 150 mg/L, and 196 mg/L, respectively, in shake flasks after 36-hour cultivation. Conclusions We achieved one gram per liter scale production of 4-coumaric acid. In addition, maximum titers of 150 mg/L of caffeic acid and 196 mg/L of ferulic acid were achieved. Phenylpropanoic acids, such as 4-coumaric acid, caffeic acid, and ferulic acid, have a great potential for pharmaceutical applications and food ingredients. This work forms a basis for further improvement in production and opens the possibility of microbial synthesis of more complex plant secondary metabolites derived from phenylpropanoic acids.